2017
DOI: 10.1186/s12891-017-1822-8
|View full text |Cite
|
Sign up to set email alerts
|

Variations in sagittal locations of anterior cruciate ligament tibial footprints and their association with radiographic landmarks: a human cadaveric study

Abstract: BackgroundThis cadaveric study aimed to demonstrate variation of the anterior cruciate ligament (ACL) tibial attachment in the sagittal plane, and to analyze the radiographic landmarks which predict the sagittal location of the ACL tibial attachment.MethodsIn 20 cadaveric knees, native ACLs were removed and the centers of the ACL tibial and femoral attachments were marked with metal pins. Full extension lateral radiographs were then obtained in each cadaveric knee. Using the full extension lateral radiographs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…Our study revealed the tibial footprint to be about 43.51% ± 3.1 from the anterior tibial cortex along the Staubli and Rauschning line. It is in accordance with the previous studies ( Table 2) and was noted to be more than 40% as per Cho et al study in the East Asian population [14]. It would be advisable to keep the center of the tibial tunnel during single bundle reconstruction between the range 37.31% and 49.71% (mean ± 2SD) as it would help in preventing a very anterior or posteriorly placed graft.…”
Section: Discussionsupporting
confidence: 89%
“…Our study revealed the tibial footprint to be about 43.51% ± 3.1 from the anterior tibial cortex along the Staubli and Rauschning line. It is in accordance with the previous studies ( Table 2) and was noted to be more than 40% as per Cho et al study in the East Asian population [14]. It would be advisable to keep the center of the tibial tunnel during single bundle reconstruction between the range 37.31% and 49.71% (mean ± 2SD) as it would help in preventing a very anterior or posteriorly placed graft.…”
Section: Discussionsupporting
confidence: 89%
“…6,8,12,34 Other methods have considered the tibial slope and used the tibial articular surface to describe a given position with a percentage along the AP depth. 6 For the mediolateral (ML) placement on an AP radiograph, few studies have described the optimal location of tunnel placement. 20,27,34 EOS is a biplanar stereoradiographic imaging modality (Figure 1) (EOS imaging, Paris, France).…”
mentioning
confidence: 99%
“… 32 Multiple reconstruction techniques target an anatomic placement of the tibial and femoral tunnels. 3 , 6 , 19 , 23 , 25 , 31 , 34 , 35 Tibial tunnels placed too far anteriorly may lead to increased graft obliquity and subsequent impingement, whereas grafts placed too far posteriorly may lead to increased anterior translational laxity. 2 , 3 , 6 , 12 , 20 , 28 Several studies have used 3-dimensional (3D) computed tomography (CT) scans to examine anatomic landmarks and to guide intraoperative tibial tunnel placement.…”
mentioning
confidence: 99%
See 2 more Smart Citations